Equality and Difference: Feminism and the Defence of Women Workers During the Great Depression - Hobbs, Margaret (Labour/Le Travailleur, 1993)
Using the theoretical framework of the feminist debates about equality and difference, this article deconstructs the arguments used by feminists and others to defend women's status as workers in the Great Depression, a period notorious for its anti-working woman sentiment. The findings suggest the false polarity of the equal rights and maternalist traditions, tracing the articulation of both in the 1930s, showing their points of intersection, and ultimately questioning their existence in any pure form.